A new approach for ultra-high adsorption of cationic methylene blue in a Zr-sulfonic-based metal–organic framework. Issue 58 (15th November 2021) - Bui, Thinh T. M.; Nguyen, Linh T.; Pham, Nha P. H.; Tran, Cuong C.; Nguyen, Loc T.; Nguyen, Tien A.; Nguyen, Hung N.; Nguyen, My V.
Abstract : A series of Zr-sulfonic-based metal–organic frameworks have been synthesized by the solvothermal method, namely VNU-17 and VNU-23. Abstract : A series of Zr-sulfonic-based metal–organic frameworks have been synthesized by the solvothermal method, namely VNU-17 and VNU-23. Particularly, VNU-17 and VNU-23 adopt the sulfonate group (SO3 − ) moieties densely packed within their structure, which can efficiently uptake MB + from wastewater. The maximum adsorption capacity for MB + onto VNU-23 is up to 1992 mg g −1 at pH = 7, which is more than five times that of activated carbon and possesses the highest value among all the reported MOF materials. In addition, VNU-23 retains the adsorption uptake of MB for at least five cycles. The adsorption isotherms and kinetic studies reveal that MB + dye adsorption onto VNU-23 fits a Langmuir isotherm and the pseudo second order kinetic model. Furthermore, the ultra-high adsorption capacity of VNU-23 for MB dye can be accounted for by the suitable pore/channel size together with electrostatic attraction and π–π interactions. These results indicate that VNU-23 can be utilized as a promising candidate for removing MB + from an aqueous medium.